Non‐Aggregation‐Induced Colorimetric Detection of Ag+ by Tetrazine‐Capped Gold Nanoparticles Based on the Formation of Au‐Ag Core‐Shell Nanoparticles. Issue 42 (14th November 2019) - Ray, Shounak; Biswas, Rima; Banerjee, Rumeli; Ghosh, Abhisek Brata; Biswas, Papu
Abstract: Recently, simple and rapid colorimetric sensing based on plasmonic nanoparticles has gained much attention as no expensive instrument required to achieve high sensitivity. In This study,  3, 6‐di(pyridin‐2‐yl)‐1, 2, 4, 5‐ s ‐tetrazine (pytz) and 3, 6‐di(pyridin‐2‐yl)‐1, 4‐dihydro‐1, 2, 4, 5‐tetrazine (H2 pytz) capped gold nanoparticles (TzAuNPs) were synthesized for the sensitive and selective colorimetric detection of Ag + . The synthesis of TzAuNPs was achieved by reaction of HAuCl4 .3H2 O in water with ethanolic solution of 3, 6‐di(pyridin‐2‐yl)‐1, 4‐dihydro‐1, 2, 4, 5‐tetrazine (H2 pytz) as reducing agent without the addition of any external stabilizing agent. As prepared TzAuNPs were characterized by FT‐IR, UV‐Vis, XRD and HRTEM techniques. The Ag + sensing mechanism is based on the formation of Au−Ag core‐shell nanoparticles (NPs). The formation of Au−Ag core‐shell NPs has been achieved in absence of any external reducing agents to observe a distinct color change from red to brown. H2 pytz molecules present on the surface of AuNPs as capping agent facilitate the reduction of Ag + . The formation of the core‐shell nanoparticles is confirmed from TEM and EDX‐particle mapping analysis. The detection limit (LOD) of the present assay is 0.56 ppb (considering signal/noise ratio=3.3) for Ag + in absence of any external reducing agent. Significant reduction of response time and much lower LOD (0.0013 ppb) have also been achieved in presence of ascorbic acid (AA) as an external reducing agent. Abstract : Facile, environment‐friendly and cost‐effective synthesis of gold nanoparticle (AuNPs) has been achieved without the addition of any external stabilizing or capping agent using 3, 6‐di(pyridin‐2‐yl)‐1, 4‐dihydro‐1, 2, 4, 5‐tetrazine (H2 pytz). The as‐synthesized tetrazine capped gold nanoparticle (TzAuNPs) utilized for selective and sensitive detection of Ag + in water through the formation of Au−Ag core‐shell nanoparticle.